Low-methoxy pectin-containing enteral nutrition in critical care for intestinal tolerance (LOME-PECT): Study protocol for a randomized controlled trial. - Shizuka Kashiwagi; Shunsuke Takaki; Yasufumi Oi; Hiroshi Honzawa; Ryo Yamamoto; Ikutaro Yamashita; Izumi Ohki; Shigeki Fujitani; Akiyoshi Nagatomi; Yuki Ohshima; Minoru Yoshida; Hideki Yoshida; et al. (PLoS ONE)
Background Enteral nutrition is preferable over parenteral nutrition for critically ill patients, but is often discontinued due to enteral feeding intolerance. Diarrhea is one of the most common causes of the discontinuation of enteral nutrition and may be attributed to the composition of enteral formulas. Dietary fiber attenuates diarrhea by normalizing the intestinal microbiota, providing energy for colonic epithelial cells, and exerting a thickening effect on intestinal contents. We herein conducted a randomized controlled trial (RCT) to test the hypothesis that the administration of an enteral formula containing low-methoxy pectin, a type of dietary fiber, more effectively ameliorates diarrhea in critically ill adult patients than a similar composition without pectin. Methods A protocol for planning a multicenter, parallel-group, open-label RCT is described herein. Enrolled patients are those ≥18 years of age with the indication of enteral nutrition by gastric access. Overall, 200 patients will be randomized into an intervention group administered an enteral formula containing low-methoxy pectin and a control group administered an enteral formula with similar components, but without pectin at a ratio of 1:1. Each enteral formula will be administered for 3 days or longer. There are no restrictions on other treatments. The primary outcome is the incidence of diarrhea as defined by Bristol Scale 5, 6, or 7. Secondary outcomes include the rate of EN failure, the survival rate, the lengths of ICU and hospital stays, and nutritional endpoints. Discussion The present study examines the effects of a low-methoxy pectin-containing enteral formula on enteral feeding intolerance, including diarrhea, in critically ill patients. The results obtained may provide new considerations regarding the selection of enteral formulas for critically ill patients. Trial registration jRCTs031230684 registered on 08 Mar 2024, https://jrct.niph.go.jp/en-latest-detail/jRCTs031230684.